Influence of chest conformation on myocardial strain parameters in healthy subjects with mitral valve prolapse - Sonaglioni, Andrea; Nicolosi, Gian Luigi; Lombardo, Michele; Gensini, Gian Franco; Ambrosio, Giuseppe (The International Journal of Cardiovascular Imaging, 2021)
Chest shape might affect myocardial strain parameters. However, the relationship between myocardial strain parameters and chest conformation has not been previously investigated in subjects with mitral valve prolapse (MVP). Between April 2019 and May 2020, 60 healthy subjects (50.1 ± 8.6 year/old, 46.6% females) with MVP and mild-to-moderate mitral regurgitation, and 60 controls matched by age, sex, and cardiovascular risk factors were consecutively studied. Participants underwent modified Haller index (MHI) assessment (ratio of chest transverse diameter over the distance between sternum and spine), and transthoracic echocardiography implemented with 2D-speckle tracking analysis. MHI was significantly greater in MVP group than controls (2.6 ± 0.35 vs 2.1 ± 0.23, p < 0.0001). Left ventricular (LV) ejection fraction was similar in MVP and controls (63.5 ± 3.7% vs 64.3 ± 3.9%, p = 0.25). LV regional and global longitudinal (GLS), circumferential (GCS) and radial strain (GRS) parameters and LV peak twist were all significantly lower in MVP compared to controls (all p < 0.0001). MVP subjects with a tight chest (MHI > 2.5, n = 30), and those with MHI ≤ 2.5 (n = 30) were then separately analyzed. A significant impairment in myocardial strain parameters and LV peak twist was documented in MVP subjects with MHI > 2.5, but not in those with MHI ≤ 2.5. MHI showed a strong inverse correlation with LV-GLS (r = − 0.85), GCS (r = − 0.84), GRS (r = − 0.84) and LV peak twist (r = − 0.94). In MVP subjects, impairment of myocardial strain parameters is not due to intrinsic reduction of cardiac contractility function, but it appears to be related to the degree of chest deformity.